The Effect of IFRS 16 on Corporate Lease Accounting in Australia - C. James Holloway; N. R. Singh (Journal of World Economy, 2025)
The implementation of IFRS 16 has significantly altered corporate lease accounting by eliminating the distinction between finance and operating leases, requiring nearly all leases to be recognized on the balance sheet. This study examines the financial and strategic implications of IFRS 16 adoption in Australia, focusing on its effects on corporate financial statements, industry-specific challenges, market reactions, and regulatory responses. The findings indicate that IFRS 16 has led to increased reported liabilities, EBITDA inflation, and shifts in corporate lease management strategies, particularly in retail, aviation, and real estate sectors, where lease obligations are substantial. In response to these changes, firms have renegotiated lease terms, reconsidered asset ownership, and adjusted financing structures to mitigate the impact of higher reported debt levels. The transition has also influenced investor sentiment, initially causing stock price volatility, as financial markets adjusted to the new lease accounting framework. Additionally, credit rating agencies have reassessed corporate leverage ratios, resulting in credit rating adjustments for some lease-intensive firms. The study further explores potential refinements in disclosure requirements and regulatory guidance, emphasizing the long-term implications of IFRS 16 on corporate financing, investment decisions, and capital structure management. The findings suggest that while IFRS 16 has enhanced financial transparency and comparability, its implementation challenges require ongoing adjustments in accounting practices, investor analysis frameworks, and corporate financial policies.